Magnetic frustration induced large magnetocaloric effect in the absence of long range magnetic order - Santanu Pakhira (Nature Portfolio, 2017)
Abstract We have synthesized a new intermetallic compound Ho2Ni0.95Si2.95 in a single phase with a defect crystal structure. The magnetic ground state of this material found to be highly frustrated without any long range order or glassy feature as investigated through magnetic, heat capacity and neutron diffraction measurements. The interest in this material stems from the fact that despite the absence of true long range order, large magnetocaloric effect (isothermal magnetic entropy change, −ΔSM ~ 28.65 J/Kg K (~205.78 mJ/cm3 K), relative cooling power, RCP ~ 696 J/Kg (~5 J/cm3) and adiabatic temperature change, ΔT ad  ~ 9.32 K for a field change of 70 kOe) has been observed which is rather hard to find in nature.